Green Tea Extract Preserves Neuromuscular Activation and Muscle Damage Markers in Athletes Under Cumulative Fatigue - Machado, Álvaro S.; da Silva, Willian; Souza, Mauren A.; Carpes, Felipe P. (Frontiers in Physiology, 2018)
A main implication of cumulative fatigue is the muscle damage that impairs neuromuscular function and training adaptations. These negative effects may limit performance when athletes exercise in consecutive days. In this regard, antioxidant supplementation has gain popularity among athletes. Green tea supplementation has been advocated as a strategy to improve exercise recovery due to the activity of its catechins with high antioxidant and anti-inflammatory potential. Here we performed a triple blinded placebo control experiment to determine the effect of green tea extract (GTE) from Camellia sinensis on muscle damage, oxidative stress, and neuromuscular activity in athletes submitted to consecutive sessions of exercise and fatigue. Sixteen trained amateur male athletes were randomly assigned to a GTE supplemented (500 mg/day) or placebo group during 15 days. Effects of supplementation were tested during repeated trials of submaximal cycling at 60% of peak power output performed after a protocol for cumulative fatigue of knee extensors. Muscle damage and oxidative stress showed lower magnitudes in response to fatigue after GTE supplementation. Placebo group showed impaired neuromuscular activity and higher muscle damage and oxidative stress compared to the GTE group during the cycling trials under fatigue. In summary, GTE supplementation showed positive effects on neuromuscular function in response to a condition of cumulative fatigue. It suggests GTE supplementation may have potential to serve as a strategy to improve performance and recovery in conditions of cumulative exercise.